The List Calculation Method of Planetary Gear Train - Zhang Lin (Jixie chuandong)
The articls divides the planetry gear train calculation process into three steps by the list analysis calculation method.The rotation speeds of basic components in each step have been put on one table.The rotation speeds of each structural component in the planetary gear train have been devised by the list calculation process.